Optimization of Finite-Alphabet Signaling for Two-User Multiaccess VLC Systems - Zhen-Yu Wang; Hong-Yi Yu; Yan-Yu Zhang; Da-Ming Wang (IEEE Photonics Journal, 2018)
Ubiquitous light emitting dioxides provide natural infrastructures for multiuser visible light communications (VLC). The current available works mainly focus on a potential assumption of the continuous signaling. In this paper, we consider a two-user multiaccess VLC system with finite-alphabet inputs. To manage the nonnegative finite-alphabet multiuser interference, we adaptively adjust the power of each user's transmitted signals to maximize the received minimum Euclidean distance. By applying the properties of Farey sequence in number theory to solve the finite-alphabet optimization, it is proved that the optimal received signal constitutes an equally spaced pulse amplitude modulation constellation, which admits a low-complexity maximum likelihood detection. Both analytical results and computer simulations demonstrate that our proposed design has substantial performance advantage over time division multiple access, especially for significant channel strength difference.